ANALYSIS ON PROCESS PARAMETERS OF SLS RAPID PROTOTYPING PROCESS - Mohamad Shiham, Najwa Sofwani (Universiti Teknologi Petronas, 2012)
This paper shows the final year project regarding the Analysis of Process Parameters for SLS Rapid Prototyping Process. Selective laser sintering (SLS) is a layered manufacturing process that builds prototypes by selective sintering of materials in powder form, like thermoplastic polymer powder, using a C02 laser. Objectives of this project are to analyze the effect of process parameters on the part accuracy and to produce the optimal model of process parameters that result in less shrinkage. Prototypes made by SLS are widely used in product development as they can be used for product testing. However the wider application of SLS has been limited due to their lack of accuracy. SLS prototypes should have high accuracy in order to satisfy functional requirement. Shrinkage is one of the major factors which influence the accuracy of the SLS parts. Therefore, continuous process improvement is necessary. Improved understanding of the parameters effects on the process response is expected to lead to process advances. The relationship between shrinkage and the various process parameters such as laser power, beam speed, hatch spacing, part bed temperature and hatch length have been investigated. Optimum shrinkage condition are obtained by analysis of variance (ANOVA) and linear regression. AN OVA is used to understand the significance of process parameters affecting shrinkage and energy density analysis is study to find its relationship with shrinkage effect. Solidworks simulation is also used to show shrinkage effect for different hatch length.